Natural sciences and human sciences. Analysis of the anti-naturalistic program - Nowak, Leszek (Anthropological Review, 1978)
The anti-naturalistic program for the human sciences is based on inductivism in the methodology of the natural sciences. According to the program, the latter apply the method of systematic observation and of induction whereas the former are constituted by specific methods (e.g., empathetic understanding). But inductivism fails as a reconstruction of scientific practice in the natural sciences because they are based on the method of idealization and, therefore, reject the classic conception of truth. A more careful analysis reveals also that the method of idealization is used in the human sciences as well. That is why the anti-naturalistic program fails. The real nature of science is the one only; it manifests merely in a different manner in different branches of it.